Inflammatory muscle disease – An update. Issue 1 (February 2020) - Baig, Sara; Paik, Julie J.
Abstract: Idiopathic inflammatory myopathies (IIM) are a heterogeneous group of inflammatory myopathies whose common feature is immune-mediated muscle injury. There are distinct subgroups including dermatomyositis (DM), polymyositis (PM), inclusion body myositis, and immune-mediated necrotizing myopathy. Antisynthetase syndrome is also emerging as a distinct subgroup with its unique muscle histopathological characteristic of perifascicular necrosis. While the newly updated EULAR/ACR Classification Criteria for IIM have brought advancements in diagnosis and the exclusion of mimickers, the use of only one autoantibody in the derivation of the schema limits its use. Similarly, while the advent of multiple novel therapeutics in the treatment of myositis has been exciting, it has also highlighted the scarcity of validated outcome measures. The purpose of our review is to highlight the updated classification criteria of myositis, newly reported clinical phenotypes associated with myositis autoantibodies, the measurement of outcomes, and emerging treatments in the field.